Angiotensin-(1-7) counteracts the transforming effects triggered by angiotensin II in breast cancer cells - Cambados, Nadia (2017)
Angiotensin (Ang) II, the main effector peptide of the renin-angiotensin system,has been implicated in multiple aspects of cancer progression such as proliferation,migration, invasion, angiogenesis and metastasis. Ang-(1-7), is a biologically activeheptapeptide, generated predominantly from AngII by the enzymatic activity ofangiotensin converting enzyme 2. Previous studies have shown that Ang-(1-7)counterbalances AngII actions in different pathophysiological settings. In this study, wehave analysed the impact of Ang-(1-7) on AngII-induced pro-tumorigenic features onnormal murine mammary epithelial cells NMuMG and breast cancer cells MDA-MB-231.AngII stimulated the activation of the survival factor AKT in NMuMG cells mainlythrough the AT1 receptor. This PI3K/AKT pathway activation also promoted epithelial?mesenchymal transition (EMT). Concomitant treatment of NMuMG cells with AngII andAng-(1-7) completely abolished EMT features induced by AngII. Furthermore, Ang-(1-7)abrogated AngII induced migration and invasion of the MDA-MB-231 cells as well aspro-angiogenic events such as the stimulation of MMP-9 activity and VEGF expression.Together, these results demonstrate for the first time that Ang-(1-7) counteracts tumoraggressive signals stimulated by AngII in breast cancer cells emerging the peptide asa potential therapy to prevent breast cancer progression.